STUDI ETNOGRAFI ORANG BANJAR DI KABUPATEN INDRAGIRI HILIR PROPINSI RIAU - Edi Susrianto Indra Putra (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
Humans as social beings must be able to interact in the midst of society. Social interaction is the most important requirement for various social activities. Interaction is a reflection of dynamic social relationships involving individual relationships, between groups, and between individuals with groups. As a pluralistic nation, Indonesia is a linkage of various elements in the form of communities and associations that have the same goal, which is to achieve a level of prosperity in accordance with human dignity and dignity. To achieve these goals, it is felt the need for a cultural foundation in the form of the potential for social capital in the attitudes and behaviors of various ethnic groups so that the objectives to be achieved can be realized. The approach taken in this study uses ethnographic studies. The use of ethnographic studies aims to determine the diversity (diversity) and specificity (particularity) of the object under study. So the final result to be obtained is to explain some aspects that are being studied, both about the ethnic origin, cultural and socio-economic forms. The Banjar people in this research concept are Banjar ethnic people or descendants from South Kalimantan who now live in Indragiri Hilir Regency.